Asian Values and Human Rights: A Vietnamese Perspective - Ngo Thi Minh Huong; Giao Cong Vu; Tam Minh Nguyen (Journal of Southeast Asian Human Rights, 2018)
This paper examines the impact of the ideology of ‘Asian Values' on the legal norms and practices that frame the recognition and protection of human rights in Vietnam. Specifically, the paper focusses on the extent to which Asian Values has been deployed to discourage the adoption of international human rights norms and practices in the context of Vietnam’s rapid economic development since the mid- 1980s. The paper first sketches the adoption of Asian Values in Vietnam’s politics and society. Cultural and political factors that have shaped the conception of human rights are reviewed. Human rights language and norms, as manifest in political ideologies, policies and laws are then analysed, with particular reference to the different versions of Vietnam’s Constitution. It is shown that both the Communist Party of Vietnam (CPV) and the State of Vietnam have clearly articulated Asian Values in formulating their conceptions of human rights. This outcome is argued to result from the fact that Vietnamese political leaders, alike with Lee Kwan Yew in Singapore, the progenitor of Asian Rights, have been strongly influenced by Confucian ideals of governance. Confucianism is not, however, the only basis for political ideas in Vietnam. Although Vietnam is a market economy it remains a one- party state controlled by the CPV. The Marxist-Leninist principles on which the current State of Vietnam was based at its inception in 1975 remain intact. This ideology was however layered onto generations of collectivist principles embodied in the dominant agrarian society. The influence of Asian Values, on the recognition of and support for human rights in Vietnam has, however, been largely negative rather than positive, especially in relation to recognising civil and political rights as codified in universal human rights instruments. Thus, the protection and promotion of human rights in Vietnam, going forward, essentially mandates eliminating the influence of Asian Values in the ideology of political leaders and in the wider society. Key words: Human rights, Asian Values, democracy, constitution, Communist Party, Vietnam